Dynamic energy budget modeling of Atlantic surfclam, Spisula solidissima, under future ocean acidification and warming. (May 2022) - Pousse, Émilien; Munroe, Daphne; Hart, Deborah; Hennen, Daniel; Cameron, Louise P.; Rheuban, Jennie E.; Wang, Zhaohui Aleck; Wikfors, Gary H.; Meseck, Shannon L.
Abstract: A dynamic energy budget (DEB) model integrating pCO2 was used to describe ocean acidification (OA) effects on Atlantic surfclam, Spisula solidissima, bioenergetics. Effects of elevated pCO2 on ingestion and somatic maintenance costs were simulated, validated, and adapted in the DEB model based upon growth and biological rates acquired during a 12-week laboratory experiment. Temperature and pCO2 were projected for the next 100 years following the intergovernmental panel on climate change representative concentration pathways scenarios (2.6, 6.0, and 8.5) and used as forcing variables to project surfclam growth and reproduction. End-of-century water warming and acidification conditions resulted in simulated faster growth for young surfclams and more energy allocated to reproduction until the beginning of the 22nd century when a reduction in maximum shell length and energy allocated to reproduction was observed for the RCP 8.5 scenario. Graphical abstract: Image 1 Highlights: ● Surfclams were exposed to OA levels inducing effects on physiological rates ● A DEB model was calibrated integrating effects on ingestion and maintenance costs ● The model was validated on Georges Bank and Mid-Atlantic Bight population data ● Effects of future OA and warming conditions projected by RCP scenarios were simulated ● Under high pCO2 emissions, DEB projects effects on growth and reproduction by 2100